Energy Saving and Pollutant Emission Reduction by Adding Hydrogen in a Gasoline-fueled Engine - Yuan-Chung Lin; Sheng-Lun Lin; Syu-Ruei Jhang; Kang-Shin Chen; Chaio-Wen Su; Chien-Er Huang (Aerosol and Air Quality Research)
Abstract Pollution reduction related to combustion engines is considered to be an important issue around the world. Hydrogen as an additive energy has been utilized for alternative fuel since it need not require any modification. Particularly, it has been considered as a sustainable option for diminishing petroleum dependence and air pollutant emissions. In this study, we investigated the tailpipe emission with hydrogen addition for different driving behavior such as cold-start, idle, urban (UDC) and extra-urban (EUDC) under New European Driving Cycle (NEDC). The results showed that urban driving could attribute the most emissions in comparison to the high speed mode. Hydrogen addition enhanced the combustion process and the average reduction rates were observed 21.6% and 65.8% for hydrocarbon (HC), 2.37% and 85.4% for carbon monoxide (CO), and 7.53% and 59.3% for nitrogen oxides (NOx) when run at UDC and EUDC, respectively. The wide flammability of hydrogen ensures a homogeneous fuel-air mixture for complete combustion and reduces the HC, CO and NOx emissions. It is noteworthy that starting with less amount of hydrogen could greatly decrease HC followed by CO and NOx. Compared to conventional gasoline (G0), the average fuel consumption was reduced by 1.3% when a small amount of hydrogen was applied as an additive fuel.